The Effect of Work Motivation, Learning Achievement, and Work Practice Results on Work Readiness - Sismoyo Sismoyo; Budi Santosa; Muhammad Sayuti (Green Publisher Indonesia, 2021)
This study aims to analyze the effect of work motivation, learning achievement and student internship results of Light Vehicle Engineering Department students on work readiness of State Vocational High School students in Cilacap Regency. This research method uses quantitative methods with data collection techniques using questionnaires and documentation. The validity test used Product Moment and the reliability test used Alpha Cronbach's. Data analysis used simple and multiple linear regression as well as relative and effective contributions. The results showed that: 1) Work motivation has an effect on job readiness, namely rx1y = 0.672; r2 = 0.452, regression coefficient = 0.702; 2) Learning achievement has an effect on job readiness, namely rx2y = 0.134; r2 = 0.018, regression coefficient = 0.009; 3) Internship has an effect on job readiness, namely rx3y = 0.610; r2 = 0.440, regression coefficient = 0.069; 4) Work motivation, learning achievement, and internship together have an effect on job readiness, namely Rx123y = 0.673; R2x123y = 0.452, multiple linear regression equation Y = 0.982x1 + 0.019x2 + 0.057x3 + 15.133 with a total effective contribution of 51.50% to job readiness.